261 Responses by heifers to development strategies using confinement or supplemented native range herbivory in Northern Great Plains. (7th December 2018) - Petersen, M; Muscha, J; Roberts, A; Duke, S
Abstract: Beef heifers thrive due to behavioral, metabolic and genetic traits. This study was designed to contrast development effects of confinement feeding or native range grazing on heart rate (HR), percent rest time (PRT), and distance traveled (DT) during December, January and February (2014 to 2016). Spring-born, crossbred heifers were stratified to 2 treatments at weaning: (1) fence line weaning on native range (NR) (N=118, 133 and 99 in 2014, 2015 and 2016 respectively) or (2) weaning in a dry lot (DL) and fed corn silage to gain 0.68 kg/d (n= 60, 67 and 62 in each yr). In December, NR heifers were allotted to 2 supplementation strategies: (NRP) access to self-fed protein supplement or (NRE) a daily energy supplement. Each month 7 heifers/treatment (n=189) were fitted with equine HR monitors (Polar Equine RS800CX) and (QSTARZ CR-Q1100P) GPS tracking recorders. Data were recorded for 48 hrs/mo and analyzed as a 3x3x3 factorial arrangement of treatments using Tukey's Mean Separation Test (P<0.05). A lower resting HR is associated with better fitness. The highest (P<0.01) resting HR was found in DL (100 ± 2.9 bpm) and lowest in NRE and NRP (81 to 77 ± 2.9 bpm). Average HR is related to energy expenditure and was influenced by yr x trt with the highest ave HR(P<0.01) occurring in 2014 in DL (116 ± 4.4 bpm) and the lowest in 2014 and 16 in NRE and NRP heifers (95.5 to 91.2 ± 4.2 bpm). Distance traveled and PRT were affected (P<0.001) by yr x mo and mo x trt. The DL heifers rested more in 2015 (38 ± 0.02%) and 2016 (40 ± 0.02%) and less in 2014 (8 ± 0.02%) whereas the NRE and NRP groups rested similarly in all 3 years (average 23 ± 0.02%). Heifer development management can impact travel and resting time causing energy expenditure and fitness differences which tended to improve with native range development.